2011
DOI: 10.1111/j.1365-2095.2009.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, partial energy balance, mantle and digestive gland lipid composition of Octopus vulgaris (Cuvier, 1797) fed with two artificial diets

Abstract: Effects of two binders (gelatine and alginate) were tested on growth, survival, partial energy balance and lipid composition of mantle and digestive gland (DG) of Octopus vulgaris. The three diets tested were given as follows: CON, (Loligo gahi) as control, GEL, composed of squid paste (L. gahi) (300 g kg−1), fish hydrolyse CPSP® (100 g kg−1) and fish meal (500 g kg−1), agglutinated with 100 g kg−1 of gelatine and ALG, composed of squid paste (L. gahi) (300 g kg−1), fish hydrolyse CPSP® (100 g kg−1) and fish m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 42 publications
(121 reference statements)
2
38
1
Order By: Relevance
“…There is evidence that this organ is used for short-term lipid storage (Boucher-Rodoni et al 1987;Fluckiger et al 2008), and it is considered to be a good indicator of nutritional status ). Furthermore, the importance of lipids in cephalopod metabolism has been demonstrated, both in early stages of development Villanueva 2000, 2003;Villanueva et al 2002) or juveniles and adults (Domingues et al 2003;Almansa et al 2006;Ferreira et al 2009;García et al 2009). …”
Section: Introductionmentioning
confidence: 96%
“…There is evidence that this organ is used for short-term lipid storage (Boucher-Rodoni et al 1987;Fluckiger et al 2008), and it is considered to be a good indicator of nutritional status ). Furthermore, the importance of lipids in cephalopod metabolism has been demonstrated, both in early stages of development Villanueva 2000, 2003;Villanueva et al 2002) or juveniles and adults (Domingues et al 2003;Almansa et al 2006;Ferreira et al 2009;García et al 2009). …”
Section: Introductionmentioning
confidence: 96%
“…Juvenile and sub-adult cephalopods are mainly fed with live prey, including crustaceans, fishes, and mollusks (Domingues et al, 2004; García García and Cerezo Valverde, 2006; Sykes et al, 2013), fisheries discards (Socorro et al, 2005; Estefanell et al, 2011), frozen prey (Ferreira et al, 2010; Sykes et al, 2013), or artificial feed stuffs (Garcia et al, 2011; Estefanell et al, 2013). Paralarvae in captivity have been traditionally fed with enriched Artemia (Iglesias et al, 2006) or supplemented with decapod zoeae, copepods, mysids, shrimps, or fish larvae, which increases survival and growth rates (Hernández-García et al, 2000; Iglesias et al, 2004, 2006; Ikeda et al, 2005; Carrasco et al, 2006; Kurihara et al, 2006; Martínez et al, 2014; Farías et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…; García et al . ; Rosas, Sanchez, Pascual, Aguila y Elvira, Maldonado & Domingues ). Recent results demonstrated that protein requirement for O. maya could be of around 60%, which is the average protein content commonly found in squid meal (Rosas et al .…”
Section: Introductionmentioning
confidence: 99%